Gambaran Karakteristik Penderita Gonore yang Melakukan Pemeriksaan Pewarnaan Gram di RS PKU Muhammadiyah Yogyakarta - Mulia Dewi Nur Haliza; Nazula Rahma Shafriani; Ratih Kusuma Dewi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Gonorrhea is a sexually transmitted disease caused by the bacterium Neisseria gonorrhoeae. This bacterium infects the urethra, cervix, anus, and throat, depending on the type of sexual contact involved. This research aimed to provide an overview of the characteristics of respondents suffering from gonorrhea who underwent examination using the Gram staining method at PKU Muhammadiyah Yogyakarta Hospital. This research employed cross-sectional method and was conducted at PKU Muhammadiyah Yogyakarta Hospital, and collected data from 24 samples between May 2022 and May 2023. The results showed that 19 patients (79,2%) tested positive. Among them, the majority of male patients showed positive results, with 18 respondents (75,0%), while only 1 female respondent (4.2%) tested positive. On the other hand, 2 male respondents (8,3%) and 3 female respondents (12,5%) tested negative. Individuals infected with gonorrhea were found to produce anti- gonococcal antibodies in their serum, semen, and cervical secretions. Specific antibody responses to gonococcal antigens were reported in various gonococcal polysaccharides and protein antigens. This research clearly shows that males are more frequently affected by gonorrhea infections. In addition, the Gram staining method provides faster results and employs a straightforward technique, which makes it the preferred choice for diagnosing gonorrhea.